PEMBUATAN INDIKATOR ASAM BASA KARAMUNTING - Cita Indira (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2015)
The most common method to get an idea about the pH of solution is to use an acid base indicator. An indicator is a large organic molecule that works somewhat like a “color dye”. Whereas most dyes do not change color with the amount of acid or base present, there are many molecules, known as acid-base indicators, which do respond to a change in the hydrogen ion concentration. A variety of indicators change color at various pH levels. A properly selected acid-base indicator can be used to visually “indicate” the approximate pH of a sample. Many indicators can be extracted from plants. Karamunting, as well as many other flowers and fruits, contain natural indicators that are sensitive to acids and bases. The color of a natural acid-base indicator depends on pH. The purpose of this research is to extract karamunting as a natural indicators and design a procedure to investigate their color changes as a function of pH. A set of standard acid and base solutions of known pH (pH = 1–14) was provided. The results was used to construct color charts of the indicators. Karamunting indicator solutions were obtained by treating this fruits with a solvent to dissolve the soluble components. The solid was crushed or ground and extracted with an appropriate solvent, such as boiling water and alcohol. Karamunting indicator solution gives red color in acidic form and blue in basic form. For the karamunting indicator paper, the most acidic form of the indicator is pink in color and the most basic form of the indicator is blue in color.